Trends in colon cancer incidence in young and older adults in Mačva Region (Serbia) - Dugandžija, Tihomir; Srećković, Marijana; Ignjatović, Vesna; Panić, Snežana; Dragičević, Igor; Hinić, Nataša (Archive of Oncology, 2022)
Objectives: Our goal was to conduct the first survey and screening of colon cancer incidence trends in the Mačva district, Serbia. Methods: Age-specific incidence of colon cancer among the > 20 years old adults that were diagnosed from 2006–2015 was analyzed using data from Cancer Registries of the Šabac Public Health Institute and Public Health Institute of Serbia. Linear model of the incidence rates and annual change in age-standardized incidence rates, by sex and age were presented. Standardized incidence ratio, based on average age-specific incidence rates of colon cancer for Šabac municipality and Central Serbia was calculated. Results: Based on the results from our study, colon cancer incidence in Šabac municipality increased in males and females in the last ten years. Risk of developing colon cancer in males and females, calculated by standardized rates ratios was 1.5 and 1.3, respectively. Linear, rising trend for age-standardized incidence rates in the population of Šabac compared to other municipalities in the Mačva district was recorded. Furthermore, standardized incidence ratios for both females and males were higher compared to data from Central Serbia (28% and 22%, respectively). Conclusion: Our study revealed increased colon cancer incidence, with a linear increase of colon cancers in young males and also in > 50 years old population.